2015
DOI: 10.1016/j.intacc.2012.10.008
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Accounting Disclosures and the Regulatory Environment on the Information Content of Earnings Announcements

Abstract: We investigate how accounting standards and the regulatory environment influence the usefulness of accounting information. Prior research finds no market reaction to earnings announcements in Mexico during the late 1990s. However, beginning in 1999, a series of regulatory changes required firms' compliance with a governance code and mandated electronic quarterly reporting. Additionally, in 2007 Mexico reissued their accounting standards to converge toward IFRS. We hypothesize that the market reacts to earnings… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 45 publications
1
15
0
Order By: Relevance
“…Another influence of the information content of earnings is the quality of the financial reporting system. Eiler, Miranda‐Lopez, and Tama‐Sweet (2015) and Olibe (2016) find that financial reporting standards and changes in regulations also affect the market reactions to earnings announcements. Landsman, Maydew, and Thornock (2012) find that the information content of earnings increased after the mandatory adoption of International Financial Reporting Standards (IFRS).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Another influence of the information content of earnings is the quality of the financial reporting system. Eiler, Miranda‐Lopez, and Tama‐Sweet (2015) and Olibe (2016) find that financial reporting standards and changes in regulations also affect the market reactions to earnings announcements. Landsman, Maydew, and Thornock (2012) find that the information content of earnings increased after the mandatory adoption of International Financial Reporting Standards (IFRS).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Environmental information disclosure is an important way for corporations to pass on their environmental responsibility performance to stakeholders and to alleviate agency problems caused by asymmetric information [25]. The level of disclosure of environmental information reflects the degree of corporate environmental responsibility of the companies.…”
Section: Corporate Environmental Information Disclosure (Ceid)mentioning
confidence: 99%
“…The first category is the studies that major in context and motivation of corporate environmental information disclosure. Liu and Anbumozhi 22 found that the present condition is that environmental information disclosure strategy of Chinese listed companies is oriented to fill up environmental concerns of government. The effort of corporate environmental information disclosure is significantly related to its environmental sensitivity.…”
Section: Background and Literature Reviewmentioning
confidence: 99%
“…By employing regression analysis to examine environmental information disclosure after a major accident in Canadian mining industry, Magness 25 found that companies that maintain themselves in the public eye through press release activity disclose more information than other companies, and companies that obtained external financing one year after accident made more disclosure than other companies. Liu and Anbumozhi 22 concluded that the better the company’s economic performance, the more the information disclosure on environmental investment and pollution control cost. Tang and Li 26 investigated that whether companies are targeting at businesses or consumers has a bigger impact on their corporate social responsibility communication than whether companies are Chinese or global.…”
Section: Background and Literature Reviewmentioning
confidence: 99%